Al-Ṭarīqah al-Naqshabandīyah al-Khālidīyah fī Minangkabau: Dirāsat Makhṭūṭat al-Manhal al-‘Adhbī li Dhikr al-Qalb - Hadi, Syofyan (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2011)
This article provides new evidence that differs from the previous studies on the presence and dynamics of the teachings of Naqshabandiyah Khalidiyah sufi order in Minangkabau. The article shows that Naqshabandiyah Khalidiyah sufi order had come and develop in Minangkabau at the beginning of the 19th century through the east cost of West Sumatra under the influence and effort made by Shaykh Isma'il al-Khalidi al-Minangkabawi. This article therefore attempts to place Shaykh Isma'il al-Khalidi al-Minangkabawi in accordance with his role as the central figure of Naqshabandiyah sufi order in Minangkabau.DOI: 10.15408/sdi.v18i2.435